Insomnia as a Symptom or a Disease - Sinan Yetkin; Hamdullah Aydin (Türk Uyku Tıbbı Dergisi, 2014)
Insomnia is an important public health problem because it has a significant negative impact on individuals’ physical, psychological, and social performance, and quality of life. It may arise directly from a sleep-wake regulatory dysfunction and/or indirectly result from comorbid psychiatric or medical conditions. It is also known that insomnia as a symptom has a negative impact on clinical structure, response to therapeutic intervention, and prognosis of co-morbid pathology. However, it has generally been viewed and treated as a symptom rather than disease. It is not always clear which insomnia cases are primary and which are secondary. But the distinction between insomnia as a disease (primary) and as a symptom (secondary) is essential for better conceptualization of the condition for etiopathogenesis, and it is also important for choosing the most appropriate and effective therapy. For these reasons, a systematic evaluation of insomnia cases is needed.